Women/migrants/victims in the male empire: The redeployment of racist and patriarchal notions in... - Muraleedharan, T. (Critical Arts: A South-North Journal of Cultural & Media Studies, 1996)
Analyzes the redeployment of racist and patriarchal notions in British Raj movies during Great Britain's colonization of India. Portrayal of migrant white women as victims of violence; Reactivation of patriarchal ideologies in response to the widespread rethinking on gender and sexuality.